An Intersectional Analysis of the English-Competency Experiences of International Teaching Assistants - Agrawal, Ashish; McNair, Lisa (Journal of International Students, 2021)
International graduate students serving as teaching assistants constitute a major component of the teaching of undergraduate students at US universities, particularly in engineering. Prior literature on these international teaching assistants (ITAs) generally characterizes their linguistic experiences as challenges. This characterization can be attributed to an institutional environment that is reluctant to accommodate diverse ways of speaking English. This study applies an intersectionality framework to explore the variations in ITAs’ English-language experiences and the influence of the academic context on these experiences using semi-structured interviews and weekly reflections collected from seven engineering ITAs over a semester. Results of data analysis suggest that ITAs’ English proficiency varies based on their prior exposure to English in their home countries, and their English competence improves through their teaching experiences in the US. Participants’ experiences also highlight a perceived expectation to not only use English while teaching but also adapt to American English.